Assessing Maternal Emotion During Child’s Pre-School Placement Among Nursing Mothers in Ilorin West, Kwara State - Ojibara, Rahmatallahi Taiye; Ola-Alani, Eniola Keji (Journal of Early Childhood Development and Education, 2026)
Background: During the process of conception, foetus largely depends on the mothers for food, protection, stability and smooth transitioning of development until delivery. Objective: The study assessed the maternal emotion in child's pre-school placement among nursing mothers in Ilorin West, Kwara State. Methods: The study adopted a descriptive survey research design, with one research question and two hypotheses. The sample population consisted of 100 nursing mothers and were randomly selected. A self-constructed questionnaire titled “Maternal Emotion Questionnaire” (MEQ) was used for data collection. The instrument was validated by experts and pre-tested through coefficient Alpha and its’ reliability Coefficient yielded a significant value of 0.76. The retrieved data were analysed using mean and standard deviation, and Analysis of Variance (ANOVA) were used to test the research question and hypotheses respectively. Results: The findings revealed that nursing mothers have high level of maternal emotion on child’s pre-school placement with a mean score of 2.95. The finding further revealed that there is a significant difference between marital status and maternal emotional experience of nursing mothers during pre-school placement (.000<0.05) and no significant difference between occupation and maternal emotional experience of nursing mothers (.251 >.05) during pre-school placement in Ilorin West, Kwara State. Conclusion: This suggests that family composition and marital status play a more critical role than employment status in shaping mothers’ emotional cues to their children’s early educational transition